Pengaruh Promosi Terhadap Keputusan Berkunjung Di Banto Royo Kecamatan Tilatang Kamang - Imam Zakira; Hijriyantomi Suyuthie (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
This motivation from research is several problems where there are still visitors who have difficulty getting information about Banto Royo, the majority of visitors have difficulty deciding to visit Banto Royo, and visitors are not satisfied after visiting Banto Royo. The research purposes conducted was to reveal the promotion impact on the decision to visit Banto Royo Park, Tilatang District. The research type used in this research is quantitative with a causal associative approach. The data type used is primary data. The research population are tourists who have visited and are currently visiting Banto Royo, Tilatang Kamang sub-district. The sample was 300 tourists using an unintentional screening strategy. The information collection strategy was carried out using a survey with a Likert scale which was tried to investigate speculation. Information from this research was handled using SPSS 26.00. The research results shownthat Promotion is in the sufficient category (75%). Likewise, the Decision to Visit is in the category was sufficient, namely (74%). There is a significant influence by Promotion on Visiting Decisions with an R square value of 0.30, with a significance of 0.000 < 0.05. This have means that there is 0.70 influenced by other factors